Access to confidential data – Implementation of a new data access option - Dummert, Sandra (International Journal of Population Data Science, 2026)
The use of confidential microdata is an important source of empirical research in the social and economic sciences. However, the high information level of these sensitive data requires clearly defined standards for data protection and IT security when accessing the data. The Research Data Centre (FDZ) of the German Federal Employment Agency (BA) at the Institute for Employment Research (IAB) provides researchers access to diverse microdata for non-commercial empirical research in the fields of social security and employment. The data portfolio includes administrative data as well as survey data and linked data products. While more anonymised data is more easily accessible, detailed data products could so far only be used during a guest stay at one of the research data centre's locations or via controlled remote data processing. However, these data access modes have various disadvantages, such as travel costs, unproductive waiting times, no direct insight into the data during controlled remote processing for data users, or the provision of hardware and administration of data access points for the research data centre. In response to the scientific community's increasing demands for flexibility and efficiency, the Research Data Centre at the IAB has established a new method of data access: the Remote Desktop Access. The Remote Desktop Access enables researchers to use confidential microdata from their workplace at their institution in compliance with data protection regulations.